“SAMBAT” SEBAGAI UPAYA MENGATASI SELF HEALING (KAJIAN AL QUR’AN SURAT RAD AYAT 28) - Laila Nadzifatus Syarifah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2023)
There is Someone who experience emotional wounds and they have problems with their psychology, then the term self-healing becomes something that is familiar to us. This self-healing becomes a process of restoring one’s self-condition. A person who experiences mental wounds cannot be healed on their own because when someone experiences this, the negative impact ends up being the impact. Actually, the forms of self-healing that can be done are very varied, one of which is the term "Sambat". Sambat itself in Indonesian society is often known as vent, expressing the contents of the heart to the closest people. The purpose of writing this article is to find out that out that the term “Sambat” can be a solution to overcoming self-healing and its connection with the Qur’an Surat Rad verse 28. This research uses a Qualitative approach with a type of library research. Data analysis techniques in this study used descriptive analysis. The results of this study are knowing about “spreading” as an effort to overcome self-healing but seen from the study of the qur’an Surah Rad verse 28 and how the role of the Qur’an is in overcoming self-healing.